TEORI POSTMODERNISME: TANTANGAN TERHADAP HUKUM DI ERA ALGORITMA TEKNOLOGI - Ramdani, Fitri Dwi (SIYASI: Jurnal Trias Politica, 2023)
Regarding the reaction of the community which shows that the case did not go through the criminal law mechanism and seems incomplete. The field of law faces new obstacles due to the rise of digital space in contemporary society. almost every activity, including in physical space. Because society has moved from the physical space to the digital space, the legal structures governing the order of social life are now present in both physical and digital spaces. With the inclusion of new platforms and professions, Covid 19 2020 is also supporting a wider campaign for tech algorithms. Regulations are needed to ensure that our digital space is beneficial for the benefit of society, and can guarantee justice for seekers, fulfilling a sense of justice in society. The ITE Law was the initial solution for the birth of this technological algorithm.